Blood Flow Restriction Following ACL Reconstruction - William Johns MD; Bright M. Wiafe BA; Sommer Hammoud MD (SAGE Publishing, 2023)
Background: Blood flow restriction (BFR) therapy is a technique that uses partial occlusion of arterial blood flow in tandem with low-load resistance training to promote an environment of metabolic stress within muscle tissue. It is hypothesized that such therapy can facilitate protein synthesis and muscle hypertrophy even in the setting of age, injury, or postoperative rehabilitation-conditions which are marred by muscle atrophy and progressive loss of function. Therefore, BFR may be a successful option to facilitate strength gains even in patients unable to perform traditional high-load resistance training. Indications: BFR therapy has been shown to be efficacious when used in healthy athletes, the elderly, or in postoperative patients undergoing rehabilitation after upper or lower extremity procedures. More specifically, BFR application in patients undergoing knee surgery has been shown to reduce muscle atrophy post operatively. Technique Description: BFR involves application of a tourniquet or occlusion cuff at 70% of the determined arterial occlusion pressure (commonly 150-180 mm Hg). The arterial occlusion pressure is calculated by observing the loss of Doppler ultrasonography signal at the pedal pulses with sequential inflation of a blood pressure cuff. This cuff should be applied as proximal as possible at the affected extremity. The patient subsequently performs 5 exercises, including 3 sets of 15 repetitions of each exercise, with 30 seconds of rest in between sets. The cuff remains inflated for all 5 exercises. Results: BFR in tandem with low-load resistance training has been shown to be effective in improving lower extremity muscle torque and mass of the quadriceps and hamstring muscles when used after knee surgery, specifically anterior cruciate ligament (ACL) reconstruction. The most commonly reported adverse outcomes after BFR include muscle soreness and sensory paresthesias; however, BFR is generally believed to be safe and acceptable for use in a broad spectrum of patients. Discussion/Conclusion: Muscle atrophy and loss of strength are hallmarks of aging, injured, and postoperative patients. Traditional means of high-intensity strength training is not feasible in these patient populations, and the use of BFR in tandem with lower intensity strength training shows promise in its ability to promote improvements in muscle strength and hypertrophy. However, more high-level research into the long-term effects, complications, and optimal BFR training regimen is warranted. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.